Prevalence of pancreatitis in cats presented to University Veterinary Hospital UPM from 2013-2014 - Lim, May Lyn (2014)
Pancreatitis is a common disease in cats and clinically important as it can lead to significant morbidity and mortality if not properly managed. However, its clinical signs are often vague and diagnosis remains challenging. In Malaysia, there are limited tests for feline pancreatitis resulting in possible underdiagnosed cases. Therefore the objectives of this study were to determine the prevalence of feline pancreatitis in cats presented to University Veterinary Hospital, UPM as well as the prevalence of concurrent pancreatitis with inflammatory bowel disease and hepatitis. Additional objective was to determine the clinical pattern of pancreatitis in cats if any. Two populations of cats were included in this study. The first population of cats included 50 clinically ill cats presented with the complaint of vomiting, diarrhea, jaundice or increased liver enzymes. The second population included 30 cats that had died or that were humanely euthanized. The pancreas, liver and small intestines were sampled for postmortem examination. The prevalence of pancreatitis in clinically ill cats was 32% (n=16) based on abnormal fPLI test results and typical ultrasonographic findings. 44% (n=7) of cats with pancreatitis had concurrent liver disease, 12% (n=2) had gastrointestinal disease and 19% (n=3) had both. There was no observable clinical pattern seen in cats diagnosed with pancreatitis. For the necropsy cases, the prevalence rate of pancreatitis was 84% (n=25) with acute pancreatitis accounting for 17% and chronic pancreatitis 67% of cases. The diagnosis of pancreatitis is difficult and should be based on a combination of compatible clinical and laboratory findings, abdominal ultrasonography, specific immunoassays for pancreatitis and histopathology.